Macroeconomic Risk Management in Nigeria : Dealing with External Shocks - Montenegro, Santiago; Claessens, Constantjin; Gooptu, Sudarshan; Imran, Mudassar; Powell, Andrew (World Bank, Washington, DC, 2012)
The Nigerian economy is highly dependent on a number of external variables beyond the control of policymakers and domestic agents. Most important among those variables is the price of oil, which is highly uncertain and determined in fluctuating international markets. With oil accounting for more than 90 percent of Nigeria's exports, 25 percent of its GDP, and 80 percent of its public revenue, a fairly small price change can have a significant impact. Largely because of changing oil prices, total exports value increased tremendously between 1972 and 1980, and then dueto a drop in world oil prices Nigerian exports value dropped back to near 1972 levels in 1986. Clearly this reliance on oil production for income generation has serious implications for its economic policy management. At present, Nigeria faces serious economic problems. To return to a path of sustainable growth and of poverty reduction, the country must address a number of critical issues, including promoting fiscal transparency and fiscal discipline, and returning to market-determined exchange and interest rates. But managing the exposure to oil revenues and external debt will also be important in establishing the foundations for the sustainability of such policies, once they are adopted.